Losing Ourselves: Active Inference, Depersonalization, and Meditation - Deane, George; Miller, Mark; Wilkinson, Sam (Frontiers in Psychology, 2020)
Disruptions in the ordinary sense of selfhood underpin both pathological and 'enlightened' states of consciousness. People suffering from depersonalization can experience the loss of a sense of self as devastating, often accompanied by intense feelings of alienation, fear and hopelessness. However, for meditative contemplatives from various traditions, “selfless” experiences are highly sought after, being associated with enduring peace and joy. Little is understood about how these contrasting dysphoric and euphoric experiences should be conceptualised. In this paper, we propose a unified account of these selfless experiences within the active inference framework. Building on our recent active inference research we propose an account of the experiences of selfhood as emerging from a temporally deep generative model. We go onto develop a view of the self as playing a central role in structuring ordinary experience by 'tuning' agents to the counterfactually rich possibilities for action. Finally, we explore how depersonalization may result from an inferred loss of allostatic control, and contrast this phenomenology with selfless experiences reported by meditation practitioners. We will show how, by beginning with a conception of self-modeling within an active inference framework, we have available to us a new way of conceptualizing the striking experiential similarities and important differences between these selfless experiences within a unifying theoretical framework. We will explore the implications for understanding and treating dissociative disorders, as well as elucidate both the therapeutic potential, and possible dangers, of meditation.